2022
DOI: 10.1016/j.cmpb.2021.106594
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation reveals that the mutant strains of SARS-CoV2 have differential structural and binding properties

Abstract: Background and Objectives Remarkable infectivity of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV2) is due to the rapid emergence of various strains which enable the virus to ruling the world. Over the course of SARS-CoV2 pandemic, the scientific communities worldwide are responding to newly emerging genetic variants. However, mechanism behind the persistent infection of these variants is still not known due to the paucity of study of these variants at molecular level. In this scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Only a few modes among the hundreds of protein modes comprise over 50% variation in the system. PCA efficiently extracts the slow (most important) modes of the protein motion that defines its biological function [85] , [86] . PCA analysis in the current study revealed that ligand-bound RdRp complexes remained in the unstable conformation state (red) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few modes among the hundreds of protein modes comprise over 50% variation in the system. PCA efficiently extracts the slow (most important) modes of the protein motion that defines its biological function [85] , [86] . PCA analysis in the current study revealed that ligand-bound RdRp complexes remained in the unstable conformation state (red) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Even though one of these patients did not have a travel history to places where SNV was more frequently found, our results highlight that the virus was probably circulating in Brazil for a considerable time before the first detection. And in fact, previous evidence indicates variants present a higher ability to escape the immune system [ 22 ], improve in binding properties of the virus on host cells [ 23 ] and become predominant over previous variants. This emphasizes the critical importance of ongoing surveillance and the regular updating of detection kits.…”
Section: Discussionmentioning
confidence: 99%
“…Essential dynamics was used to obtain the key motions along with first three principal components (PCs) which comprise maximum motions. It will help us to study the biological significant motions related to protein functions [ 38 , 39 ]. A covariance matrix was created after excluding translational and rotational movement from the trajectories.…”
Section: Methodsmentioning
confidence: 99%